Investigation of Frequency Response Sharing-Induced Power Oscillations in VSC-HVDC Systems for Asynchronous Interconnection - Ke Wang; Chunguang Zhou; Yiping Chen; Yan Guo; Zhantao Fan; Zhixuan Li (Energies)
Low-frequency power oscillations (LFPOs) may occur in voltage source converter-based high-voltage direct current (VSC-HVDC) systems when providing frequency support to asynchronously interconnected power grids. This phenomenon has been observed in the LUXI back-to-back (BTB) VSC-HVDC project in China and results from insufficient damping, which may threaten the stability of the overall power system. To better understand and address this problem, this study investigates the root causes of LFPOs and evaluates how different parts of the system affect damping. A combined approach using small-signal modeling and the damping torque method is developed to analyze the damping behavior of DC power in VSC-HVDC systems. Results show that LFPOs are caused by the interaction between VSC-based frequency control and the dynamic response of synchronous generators (SGs). The turbine and governor systems in SGs help stabilize the system by providing positive damping, whereas the DC voltage-controlled VSC station introduces negative damping. The findings are supported by detailed simulations using a modified IEEE 39-bus test system, demonstrating the effectiveness of the proposed analysis method.